2003
DOI: 10.1159/000073450
|View full text |Cite
|
Sign up to set email alerts
|

Eating Disorders and Body Image Disturbances among Ballet Dancers, Gymnasium Users and Body Builders

Abstract: Background: Eating disorders are frequent among elite performers of certain sports or physical activities; however, little is known about non-professional performers. Method: 113 female non-elite ballet dancers, 54 female gymnasium users, 44 male non-competitive body builders, 105 female controls and 30 male controls were evaluated using the Body Uneasiness Test, the State-Trait Anxiety Inventory, the Beck Depression Inventory, and the Eating Disorder Examination 12th edition (EDE-12). Results: Non-elite balle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
69
0
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(85 citation statements)
references
References 36 publications
7
69
0
8
Order By: Relevance
“…BUT scores were analyzed by considering the total score of the test (Global Severity Index), the number of body parts disliked (positive symptoms total) and the mean intensity of dislike of all disliked body parts (Positive Symptom Distress Index). 41 The internal consistency of BUT is satisfactory in terms of both the significant homogeneity (indicated by the Item-Total Correlations) and the clearly one-dimensional structure shown by each of the subscales according to the analyses of the main components. The levels of Cronbach's a coefficients range between 0.69 and 0.90.…”
Section: Methodsmentioning
confidence: 89%
“…BUT scores were analyzed by considering the total score of the test (Global Severity Index), the number of body parts disliked (positive symptoms total) and the mean intensity of dislike of all disliked body parts (Positive Symptom Distress Index). 41 The internal consistency of BUT is satisfactory in terms of both the significant homogeneity (indicated by the Item-Total Correlations) and the clearly one-dimensional structure shown by each of the subscales according to the analyses of the main components. The levels of Cronbach's a coefficients range between 0.69 and 0.90.…”
Section: Methodsmentioning
confidence: 89%
“…Within male body image research, bodybuilding has been of particular focus. Bodybuilders have been reported to experience distorted body image (Ravaldi et al, 2003), body dissatisfaction (Esco, Olson, & Williford, 2005), exercise dependence (Smith & Hale, 2005), and disordered eating and psychological characteristics similar to eating disorder sufferers (Mangweth et al, 2004). Based on these findings, the importance of investigating male body image concerns within the gym subculture is evident, particularly given the increasing number of males striving for masculine physiques.…”
mentioning
confidence: 99%
“…These findings seem partially in contrast with other studies, in which a group of bodybuilders showed a high degree of body uneasiness (rAvAldi et al, 2003). On the other hand, it was also proved that strength training may produce an improvement in BI through important changes in body shape, such as muscle definition and muscular tone enhancement (zABinSKi et al, 2001).…”
Section: Discussionmentioning
confidence: 69%
“…The BI distress of some gymnasts and ballet dancers (rAvAldi et al, 2003) and the muscle dysmorphia of some bodybuilders (olivArdiA, 2001) are well known examples of negative influences. Otherwise, it is well recognized that athletes and physically active persons are generally more satisfied with their bodies in comparison to sedentary, inactive people.…”
Section: Introductionmentioning
confidence: 99%